IMPLEMENTASI METODE QIROATI DALAM PEMBELAJARAN AL-QUR'AN - Latifah, Umi; Amirudin, Noor (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
In the context of education in Indonesia, Al-Qur'an education does not receive serious enough attention because most children and adolescents in the surrounding community still do not pay attention to the science of recitation and makhorijul letters when reading the Qur'an, so a a method to improve reading of the Qur'an, namely the Qiro'ati method at TPQ Al Irsyadiyah. The Qiro'ati method is a method of teaching reading the Qur'an directly according to its tartil and tajwid. The purpose of this study is to describe the Implementation of the Qiro'ati Method in Al-Qur'an Learning at TPQ Al Irsyadiyah Dermolemahbang Lamongan. Data collection methods used in the form of observation and, interviews using the validity of triangulation data sources and techniques. The technique of determining the informants used purposive sampling using data analysis techniques, namely data reduction, data presentation and conclusions. The results of the study show that implementing the Qiro'ati Method program, teachers must have a shahadah certificate through the process of developing teaching practice methodologies and teachers must also follow the rules of Qiro'ati. For the implementation of early learning there are tawasul, collective prayer, muroja'ah (asmaul husna, hadith and prayers), 2) Core learning 15 minutes classical read see later, 30 minutes individually 3) Read prayers after learning then, 15 minutes for the process memorizing and checking what has been written